CONCEPTION RATE PADA SAPI POTONG DI KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Fajar Fitraldi Dirgahayu; Madi Hartono; Purnama Edy Santosa (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The aim of this research was to determine the conception rate and the factors value that affect in beef cattle in the district Jati Agung, South Lampung regency. This study was conducted in April 2014 to 1,410 head of beef cattle belonging to 776 farmers. The research used a survey method with primary and secondary data. Analysis data used regression analysis with SPSS ( Statistic Packet for Social Science) program.The results showed that the conception rate in the district Jati Agung is a great identity for 36.03 ± 1.16. Factors that effect conception rates in beef cattle in the district Jati Agung is distance between the cowshed with house that negatively assosiated with factor value 0.003, number of factor concentrate that negatively assosiated with factor value of 0.027, amount of forage factor that negatively assosiated with factor value 0.003, a large area of the cage that negatively assosiated with factor value 0.020, and amount of beef cows that maintained that negatively assosiated with factor value 0.049 and a positive association was never followed a course that positively assosiated with factor value 0.112. The factors that influence conception rates in beef cattle farm level is great on long weaning period that negatively assosiated with factor value 0.013, mating postpartum that positiively assosiated with factor value 0.376, calving interval that negatively assosiated with factor value 0.412, the age of cattle that positively assosiated with factor value 0.006, the first estrus postpartum artificial insemination that positively assosiated with factor value 0.133 and time to insemination that negatively assosiated with factor value 0,406.